2005
DOI: 10.1088/0953-4075/38/4/009
|View full text |Cite
|
Sign up to set email alerts
|

Variation in resonant Auger yields into the1G4sdotnlstates of Kr across the L3threshold

Abstract: Resonant Auger transitions into 1 G 4 •nl states following Kr 2p 3/2 electron excitation have been measured using monochromatized undulator radiation and a hemispherical electron energy analyzer. A clear identification of electron peaks was made for the 1 G 4 •5s, 1 G 4 •4d, 1 G 4 •5d and so forth when the photon energy approached to the ionization threshold. The formation of the 1 G 4 •4d state was found over a relatively wide energy range across the threshold, because of the short lifetime of the 2p hole and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
(96 reference statements)
1
14
0
Order By: Relevance
“…The intensity of the monochromatized incident photon beam during the measurement was monitored by collecting the drain current of the postfocusing mirror in the beamline. An electron spectrometer used consists of a hemispherical electron spectrometer (Gammadata Scienta, SES-2002) fitted to a gas cell (GC-50) by way of a multielement lens in a differentially pumped chamber [10]. Sample gas of SiF 4 was supplied into the gas cell and the gas density observed in the chamber during the measurements was 2×10 −4 Pa.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intensity of the monochromatized incident photon beam during the measurement was monitored by collecting the drain current of the postfocusing mirror in the beamline. An electron spectrometer used consists of a hemispherical electron spectrometer (Gammadata Scienta, SES-2002) fitted to a gas cell (GC-50) by way of a multielement lens in a differentially pumped chamber [10]. Sample gas of SiF 4 was supplied into the gas cell and the gas density observed in the chamber during the measurements was 2×10 −4 Pa.…”
Section: Methodsmentioning
confidence: 99%
“…In the photoexcitation of an inner-shell electron into a vacant orbital, resonant Auger electrons emerge [5][6][7][8][9][10]. The final state in a spectator-type process is represented by a spectator electron and a doubly charged ion core, which is assumed to be the same as the state in the normal Auger (NA) decay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photon energy resolution during the measurements was set at about 2000. Photon energy was calibrated for the peak of the excitation of the Kr2p 3/2 electron into the 5s orbital, 1673.8 eV (Okada et al, 2005). The monochromatized photon beam crossed the sample gas beam ejected through a 1/16-in.…”
Section: Methodsmentioning
confidence: 99%
“…The energy positions derived in this study were similar to those obtained earlier while the observed intensity ratios revealed differences. Finally, the resonant Kr 2p −1 nl Auger spectra were studied by Nagaoka et al and Okada et al [20,21].…”
Section: Introductionmentioning
confidence: 99%